From Poverty Alleviation to Access Education and Build Aspirations: The Impact of Shift-Persist Strategies on Entrepreneurship Opportunity Development Among Lower Social Class - Aiwen Niu; Changchun Gao; Chenhui Yu (SAGE Open)
Entrepreneurship at the base of the pyramid has profound implications for economic development in impoverished regions. Building upon Timmons’ three-factor theory of entrepreneurship and the resource conservation theory, this study adopts the transition-persistence strategy of entrepreneurs from lower social classes as the focal point, with psychological capital and resourcefulness as dual pathways, constructing an antecedent model of entrepreneurial opportunity development. To investigate this model, the study utilized a two-phase empirical approach. The first study involved a small-scale experiment with 73 participants from specific regions to pilot the investigation, while the second study distributed 405 questionnaires to test the mechanisms of action and boundaries of influence of the shift-persist strategy. Findings revealed that cognitive interventions significantly influenced entrepreneurs’ shift-persist strategy and their levels of entrepreneurial opportunity development. Moreover, psychological capital and resourcefulness partially mediated the relationship between the shift-persist strategy and entrepreneurial opportunity development. Furthermore, market uncertainty exhibited significant positive moderating effects only in the psychological capital pathway, whereas it did not significantly impact the resourcefulness pathway. This study offers a novel perspective for understanding the entrepreneurial behavior of individuals from lower social classes and provides valuable insights for entrepreneurial policies and practices.